A cognitive rooting of Predictive literature - Behnas, Chahrazad (Journal of Human Sciences, 2021)
The writer or creator is primarily a human being, but is more sensitive. It is affected by the facts of events and life, lives it and suffers from its events and pigmented by its facts that many may pass through quickly, and her creativity is never a form of excessive imagination, or a way to sail on a journey of unseen and intellectual absurdity, rather they are a visionary journey, which he reflects in an artistic character that marries imagination And reality, depending on the data of language, techniques of story, novel and music of words, to reveal the defects, to avoid error and to develop solutions to urgent problems.